Evaluating high-throughput assays for pesticide ecological risk assessment - Leah Sattler; Michelle Embry; Scott Glaberman (Regulatory Toxicology and Pharmacology, 2025)

The Botanical Safety Consortium: collaborative effort to improve botanical safety methods - Connie Mitchell; Michelle Embry; Julie Krzykwa; Amy Roe; Olaf Kelber (Phytochemistry Letters, 2025)

Control performance of Amphibian Metamorphosis Assays with Xenopus laevis - James R. Wheeler; Raechel Puglisi; Adriana C. Bejarano; Zhenglei Gao; Laurent Lagadic; Scott Glaberman; Constance A. Mitchell; Natalie Burden; Valentin Mingo; Scott G. Lynn; Michelle R. Embry (Regulatory Toxicology and Pharmacology, 2025)

Advancing botanical safety: A strategy for selecting, sourcing, and characterizing botanicals for developing toxicological tools - Suramya Waidyanatha; Bradley J. Collins; Tim Cristy; Michelle Embry; Stefan Gafner; Holly Johnson; Josh Kellogg; Julie Krzykwa; Siheng Li; Constance A. Mitchell; Esra Mutlu; Sarah Pickett; et al. (Food and Chemical Toxicology, 2024)

Neuroactivity screening of botanical extracts using microelectrode array (MEA) recordings - Regina G.D.M. van Kleef; Michelle R. Embry; Constance A. Mitchell; Remco H.S. Westerink (Food and Chemical Toxicology, 2024)

Quantitative Structure Use Relationships: Highlights from a technical summit meeting - Rosemary T. Zaleski; Andreas Ahrens; Jon A. Arnot; Richard A. Becker; Mark Bonnell; Sean Collins; Paul DeLeo; Peter Egeghy; Michelle Embry; Todd Gouin; Kristin Isaacs; Elke Jensen (Regulatory Toxicology and Pharmacology, 2023)

Improving the rigor and utility of botanical toxicity studies: Recommended resources - Deval Patel; Barbara C. Sorkin; Constance A. Mitchell; Michelle R. Embry; Sharline Rina-Kong; Rebecca E. Adams; Emily R. DeTemple; Aalekhya Reddam; Stefan Gafner; Olaf Kelber; Cynthia V. Rider; Hellen Oketch-Rabah; et al. (Regulatory Toxicology and Pharmacology, 2023)

Correction: A Critical Review of Bioaccumulation and Biotransformation of Organic Chemicals in Birds - Dave T. F. Kuo; Barnett A. Rattner; Sarah C. Marteinson; Robert Letcher; Kim J. Fernie; Gabriele Treu; Markus Deutsch; Mark S. Johnson; Sandrine Deglin; Michelle Embry (Reviews of Environmental Contamination and Toxicology, 2022)

A Critical Review of Bioaccumulation and Biotransformation of Organic Chemicals in Birds - Dave T. F. Kuo; Barnett A. Rattner; Sarah C. Marteinson; Robert Letcher; Kim J. Fernie; Gabriele Treu; Markus Deutsch; Mark S. Johnson; Sandrine Deglin; Michelle Embry (Reviews of Environmental Contamination and Toxicology, 2022)
A literature review of bioaccumulation and biotransformation of organic chemicals in birds was undertaken, aiming to support scoping and prioritization of future research. The objectives were to characterize available bioaccumulation/biotransformation data, identify knowledge gaps, determine how extant data can be used, and explore the strategy and steps forward. An intermediate approach balanced between expediency and rigor was taken given the vastness of the literature. Following a critical review of > 500 peer-reviewed studies, > 25,000 data entries and 2 million information bytes were compiled on > 700 organic compounds for ~ 320 wild species and 60 domestic breeds of birds. These data were organized into themed databases on bioaccumulation and biotransformation , field survey , microsomal enzyme activity , metabolic pathway , and bird taxonomy and diet . Significant data gaps were identified in all databases at multiple levels. Biotransformation characterization was largely fragmented over metabolite/pathway identification and characterization of enzyme activity or biotransformation kinetics. Limited biotransformation kinetic data constrained development of an avian biotransformation model. A substantial shortage of in vivo biotransformation kinetics has been observed as most reported rate constants were derived in vitro. No metric comprehensively captured all key contaminant classes or chemical groups to support broad-scope modeling of bioaccumulation or biotransformation. However, metrics such as biota-feed accumulation factor, maximum transfer factor, and total elimination rate constant were more readily usable for modeling or benchmarking than other reviewed parameters. Analysis demonstrated the lack of bioaccumulation/biotransformation characterization of shorebirds, seabirds, and raptors. In the study of bioaccumulation and biotransformation of organic chemicals in birds, this review revealed the need for greater chemical and avian species diversity, chemical measurements in environmental media, basic biometrics and exposure conditions, multiple tissues/matrices sampling, and further exploration on biotransformation. Limitations of classical bioaccumulation metrics and current research strategies used in bird studies were also discussed. Forward-looking research strategies were proposed: adopting a chemical roadmap for future investigations, integrating existing biomonitoring data, gap-filling with non-testing approaches, improving data reporting practices, expanding field sampling scopes, bridging existing models and theories, exploring biotransformation via avian genomics, and establishing an online data repository.